KARAKTERISTIK STRUKTUR DAN KEBAHASAAN TEKS BERITA KARYA SISWA KELAS VIII SMP NEGERI 12 PADANG - Firdaus, Wildan; Tamsin, Andria Catri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT The Characteristics of Structure and Language News Texts of Class VIII Students of  Junior High School  Number 12 Padang. Thesis: Indonesian Language Study Program, Indonesian Language and Literature Department, Faculty of Language and Art,  Universitas Negeri Padang. This research is motivated by many facts found in the field that the obstacles faced by teachers and students in implementing teaching news writing skills. Many students complain the difficulties starting their writing. In addition, the provision of facilities and the application of less creative teaching methods were the main obstacles encountered. This results in boredom in students when assigned to write a news. In fact, the use of an interesting method is one way that can be done to motivate students' interests to write and develop their reasoning. This was found at  Junior High School  Number 12 Padang. Indonesian language teacher at  Junior High School  Number 12 Padang, Afdawati, S.Pd., revealed the problem in a pre-research interview on January 23, 2019. This study illustrates abouth the ability of students of class VIII  Junior High School  Number 12 Padang in understanding and making news texts. Kata Kunci: bahasa Indonesia, pembelajaran, teks berita